An electric field-based approach for quantifying effective volumes and radii of chemically affected space. Issue 22 (19th May 2022) - Mroz, Austin M.; Davenport, Audrey M.; Sterling, Jasper; Davis, Joshua; Hendon, Christopher H.
Abstract : Computing atomic and molecular volumes from DFT and ab initio -based electric fields. Abstract : Chemical shape and size play a critical role in chemistry. The van der Waals (vdW) radius, a familiar manifold used to quantify size by assuming overlapping spheres, provides rapid estimates of size in atoms, molecules, and materials. However, the vdW method may be too rigid to describe highly polarized systems and chemical species that stray from spherical atomistic environments. To deal with these exotic chemistries, numerous alternate methods based on electron density have been presented. While each boasts inherent generality, all define the size of a chemical system, in one way or another, by its electron density. Herein, we revisit the longstanding problem of assessing sizes of atoms and molecules, instead through examination of the local electric field produced by them. While conceptually different than nuclei-centered methods like that of van der Waals, the field assesses chemically affected volumes . This approach implicitly accounts for long-range fields in highly polar systems and predicts that cations should affect more space than neutral counterparts.